Expression of highly active chondroitin 4-O-sulfotransferase-1 in Escherichia coli by a trigger factor fusion protein expression system. (April 2022) - Takashima, Makoto; Suzuki, Kiyoshi; Mochizuki, Hideo; Uemura, Satoshi; Inokuchi, Jin-ichi; Eguchi, Tadashi
Abstract: Chondroitin 4- O -sulfotransferase-1 (C4ST-1) is a key enzyme for the biosynthesis of chondroitin sulfate A (CSA). Several past reports have evaluated the expression of C4ST-1 in bacteria. Since N -glycosylation is critical for the activity of C4ST-1, its activity was quite low. Here, we established a method for inducing a high expression of recombinant C4ST-1 in Escherichia coli ( E. coli ) by using a trigger factor (TF) fusion system. This approach enabled the expression of 18.9 ± 5.0 mg/L of TF-fused C4ST-1 (TF-C4ST-1). Although TF-C4ST-1 does not undergo N -glycosylation, the k cat /K m was approximately 60% of that of N -glycosylated C4ST-1. By using TF-C4ST-1 and chondroitin (CH) obtained from the culture of another recombinant E. coli, we succeeded in the 10-mg-scale preparation of CSA consisting almost entirely of the CSA disaccharide, GlcAβ1–3GalNAc(4S). These results demonstrated that the expression of C4ST-1 in bacteria is sufficient to achieve the long-term goal of manufacturing non-animal-derived CSA. Graphical Abstract: ga1 Highlights: Trigger factor fused C4ST-1 (TF-C4ST-1) was expressed in Escherichia coli . Although TF-C4ST-1 has no N -glycans, it possesses sulfotransferase activity. The k cat /K m of TF-C4ST-1 was approximately 60% of that of N -glycosylated C4ST-1. Using TF-C4ST-1, 10-mg-scale preparation of non-animal-derived CSA was possible. TF-C4ST-1 has sufficient function for manufacturing non-animal-derived CSA.